Regionalism without Regions : Reconceptualizing Ukraine's Heterogeneity - Myshlovska, Oksana; Schmid, Ulrich, 1965- (New York : Central European University Press, 2019)
"This collective volume shows how Ukraine can best be understood through its regions and how the regions must be considered against the background of the nation. The overarching objective of the book is to challenge the dominance of the nation-state paradigm in the analyses of Ukraine by illustrating the interrelationship between national and regional dynamics of change. The authors--historians, sociologists, anthropologists, economists, literary critics and linguists from Ukraine, Poland, Switzerland, Germany and the USA--explicitly go beyond the perspective of an entity defined by traditional political borders and cultural, economic, historical or religious stereotypes. The research project that led to the composition of the book combined quantitative (statistical surveys conducted across Ukraine) and qualitative (in-depth interviews and focus-group discussion) methods. The authors came to the conclusion that regionalism as a defining phenomenon of Ukraine is more prominent than the regions themselves. This approach regards Ukraine as a construct in flux where different discourses intersect, concur and eventually merge through the lenses of various disciplines and methodologies"--
Introduction / Oksana Myshlovska, Ulrich Schmid and Tatjana Hofmann -- The regional differentiation of identities in Ukraine : how many regions? / Maria Lewicka and Bartłomiej Iwańczak -- The Ukrainian past and present : legacies, memory and attitudes / Andre Liebich, Oksana Myshlovska, Viktoriia Sereda, with Oleksandra Gaidai And Iryna Sklokina -- Language(s) in the Ukrainian regions : historical roots and the current situation / Juliane Besters-Dilger, Kateryna Karunyk and Serhii Vakulenko -- Literary mediascapes in Ukraine / Tatjana Hofmann, Anna Chebotarova, Alexander Kratochvil and Ulrich Schmid -- Religion and the cultural geography of Ukraine / Catherine Wanner and Viktor Yelensky -- Recent regional economic development in Ukraine : does history help to explain the differences? / Yaroslav Prytula, Natalia Pohorila, Svitlana Tyahlo, Elena Denisova-schmidt and Martin Huber -- Ukraine in 2013-2014 : a new political geography / Yaroslav Hrytsak -- Renegotiating "Ukrainian identity" at the Euromaidan / Anna Chebotarova -- Conclusion / Oksana Myshlovska.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: National characteristics, Ukrainian; Cultural pluralism -- Ukraine; Political geography; Regionalism -- Ukraine; Ukraine -- Social conditions; Ukrainians; Ukrainiens; Diversité culturelle -- Ukraine; Géographie politique; Régionalisme -- Ukraine; Ukraine -- Conditions sociales; HISTORY -- Europe -- Eastern; Ukrainians; Cultural pluralism; National characteristics, Ukrainian; Political geography; Regionalism; Social conditions; Ukraine; Cultural studies, Economic development, Ethnicity, Language policies, Regionalism, Ukraine; Electronic books